Dynamic Development of Viral and Bacterial Diversity during Grass Silage Preservation - Johan S. Sáenz; Bibiana Rios-Galicia; Bianca Rehkugler; Jana Seifert (Viruses, 2023)
Ensilaging is one of the most common feed preservation processes using lactic acid bacteria to stabilize feed and save feed quality. The silage bacterial community is well known but the role of the virome and its relationship with the bacterial community is scarce. In the present study, metagenomics and amplicon sequencing were used to describe the composition of the bacterial and viral community during a 40-day grass silage preservation. During the first two days, we observed a rapid decrease in the pH and a shift in the bacterial and viral composition. The diversity of the dominant virus operational taxonomic units (vOTUs) decreased throughout the preservation. The changes in the bacterial community resembled the predicted putative host of the recovered vOTUs during each sampling time. Only 10% of the total recovered vOTUs clustered with a reference genome. Different antiviral defense mechanisms were found across the recovered metagenome-assembled genomes (MAGs); however, only a history of bacteriophage infection with Lentilactobacillus and Levilactobacillus was observed. In addition, vOTUs harbored potential auxiliary metabolic genes related to carbohydrate metabolism, organic nitrogen, stress tolerance, and transport. Our data suggest that vOTUs are enriched during grass silage preservation, and they could have a role in the establishment of the bacterial community.